Should We Prevent Optimific Wrongs?. Issue 2 (21st September 2015) - MOGENSEN, ANDREAS L.
Abstract : Most people believe that some optimific acts are wrong. Since we are not permitted to perform wrong acts, we are not permitted to carry out optimific wrongs. Does the moral relevance of the distinction between action and omission nonetheless permit us to allow others to carry them out? I show that there exists a plausible argument supporting the conclusion that it does. To resist my argument, we would have to endorse a principle according to which, for any wrong action, there is some reason to prevent that action over and above those reasons associated with preventing harm to its victim(s). I argue that it would be a mistake to value the prevention of wrong acts in the way required to resist my argument.